The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1063/1.1571057
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Properties, ΔfH°(298.15 K), S°(298.15 K), and Cp°(T), of 1,4-Dioxin, 2,3-Benzodioxin, Furan, 2,3-Benzofuran, and Twelve Monochloro and Dichloro Dibenzo-p-dioxins and Dibenzofurans

Abstract: Values for ΔfH°(298.15 K), S°(298.15 K), and Cp°(T) (5⩽T/K⩽6000) are computed by density functional B3LYP/6-31G(d,p) and B3LYP/6-311+G(3df,2p) calculation methods for 12 monochloro and dichloro dibenzo-p-dioxins and dibenzofurans: 1-chloro dibenzo-p-dioxin, 2-chloro dibenzo-p-dioxin, 1,6-dichloro dibenzo-p-dioxin, 1,8-dichloro dibenzo-p-dioxin, 1,9-dichloro dibenzo-p-dioxin, 2,8-dichloro dibenzo-p-dioxin, 3-chloro dibenzofuran, 4-chloro dibenzofuran, 1,6-dichloro dibenzofuran, 3,6-dichloro dibenzofuran, 3,7-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Each ortho-or meta-Cl/Cl interaction is assumed to reduce the enthalpy of formation by 1.8 kcal/mol and 0.60 kcal/mol respectively. These GA rules of Dorofeeva et al [218] were reviewed by Zhu and Bozzelli [221]. They recommended adding 2.6 and 3.6 kcal/mol for each ortho-and meta-chlorine interaction in dibenzo-p-dioxin, respectively.…”
Section: Thermochemical Parameters and Their Influence On Pcdd/f Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Each ortho-or meta-Cl/Cl interaction is assumed to reduce the enthalpy of formation by 1.8 kcal/mol and 0.60 kcal/mol respectively. These GA rules of Dorofeeva et al [218] were reviewed by Zhu and Bozzelli [221]. They recommended adding 2.6 and 3.6 kcal/mol for each ortho-and meta-chlorine interaction in dibenzo-p-dioxin, respectively.…”
Section: Thermochemical Parameters and Their Influence On Pcdd/f Formmentioning
confidence: 99%
“…These comparisons were carried out by adjustments of vibrational frequencies, moments of inertia and other properties through transformation of the force constants from polycyclic hydrocarbons including dibenzofuran and dibenzo-p-dioxin. Isodesmic reactions were used by Zhu and Bozzelli [221] to determine the enthalpies of formation of various dioxin congeners using DFT (at the B3LYP/6-311 þ G(3df,2p)// B3LYP/6-31G(d) level). Their estimates for the enthalpies of formation of DF and DD were 13.9 and À14.4 and kcal/mol, respectively, in excellent agreement with experimental values.…”
Section: Thermochemical Parameters and Their Influence On Pcdd/f Formmentioning
confidence: 99%
“…These isodesmic reactions utilize experimental values of Δ f H ° 298 for phenol (−96.3 ± 0.59 kJ mol –1 ), o -chlorophenol (−131 kJ mol –1 ), o -bromophenol (−78 ± 1.9 kJ mol –1 ), p -chlorophenol (−145.5 ± 8.4 kJ mol –1 ), p -bromophenol (−69.3 ± 2.1 kJ mol –1 ), benzene (82.9 ± 0.9 kJ mol –1 ), bromobenzene (105.4 ± 4.20 kJ mol –1 ), and chlorobenzene (52.4 ± 0.42 kJ mol –1 ) Table provides calculated reaction enthalpies for R1 (Δ R1 H ° 298 ) and R2 (Δ R2 H ° 298 ) and Δ f H ° 298 of the target species.…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of the B3LYP functional in the study of high temperature combustion reactions has also been widely demonstrated [24][25][26]. This is also the case regarding PCDD/F heats of formation [27]. The Gaussian09 [28] program was used to perform all structural and energy calculations.…”
Section: Methodsmentioning
confidence: 99%